Fractionalization and the Size of Government - Jo Thori Lind (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper studies the joint effect of fractionalization and inequality on the size of government. Within a political economy model of tax determination, I study the effect of voters with a group-based social conscience, so they care more about the well-being of those belonging to their own group than the rest of the population. Under general assumptions, both fractionalization and group antagonism reduce the support for redistribution. Whereas within group inequality increases support for redistribution, inequality between groups have the opposite effect. All these results hold even if a poor group is in majority. Using a panel data set for the US constructed from micro data, I find support for the hypothesis that within race inequality increases and between group inequality decreases redistribution.
Keywords: 330; fractionalization; political economy; inequality; redistribution; race